A Webometric Study of Selected International Library Association Websites An Evaluative Study - Dhar, Prasenjit; Gayan, Mithu Anjali (DESIDOC Journal of Library & Information Technology, 2022)
The official website of any organisation provides authentic information about it. The current study is a novel attempt to explore international library association websites and assess those websites based on web content evaluation and webometric parameters. Several library websites have been analysed by researchers. However, the same has not been attempted regarding the library association website at the international level. International library associations indexed by American Library association’s website were taken as the sample. Data were collected using a link analysis tool from https://moz.com/ which helps in determining Domain Authority, Page Authority, in-links, and out-links; Google was used for the links. Official websites of the library associations were visited for the website evaluation with a well-structured checklist having 19 criteria. International Association of Law Libraries is found to have the highest simple web impact factor and external web impact factor. In contrast, the Association of Jewish Libraries has the highest internal web impact factor. All the websites examined in this study are hosted under the .org domain. The study revealed that 7 out of 8 (87.5 %) international library association websites’ Domain Authority and Page Authority is below 50. Essential information like customer service, currency, and FAQ are not available on the websites. The results of this study will help the library associations in re-structuring and better maintenance of their website.